Twenty-first-century gateways : immigrant incorporation in suburban America - Singer, Audrey; Hardwick, Susan Wiley; Brettell, Caroline (Washington, D.C. : Brookings Institution Press, 2008)
"Focuses on the fastest-growing immigrant populations among "second-tier" metropolitan areas. Examines the changes wrought by these new suburban settlement patterns and provides comparative analysis of immigration trends and local policy responses in these gateways. Case examples explore the challenges of newcomer integration, as well as immigration's impact on suburban infrastructure"--Provided by publisher.
Foreword / Henry Cisneros -- Acknowledgments -- Twenty-first-century gateways : an introduction / Audrey Singer -- Toward a suburban immigrant nation / Susan W. Hardwick -- "Big D" : incorporating new immigrants in a sunbelt suburban metropolis / Caroline B. Brettell -- Diverging trajectories : Asian and Latino immigration in metropolitan Phoenix / Alex Oberle and Wei Li -- Unsettled in the suburbs : Latino immigration and ethnic diversity in metro Atlanta / Mary E. Odem -- Edge gateways : immigrants, suburbs, and the politics of reception in metropolitan Washington / Marie Price and Audrey Singer -- Immigrant space and place in suburban Sacramento / Robin Datel and Dennis Dingemans -- Impediments to the integration of immigrants : a case study in the Twin Cities / Katherine Fennelly and Myron Orfield -- "Placing" the refugee diaspora in suburban Portland, Oregon / Susan W. Hardwick and James E. Meacham -- Austin : immigration and transformation deep in the heart of Texas / Emily Skop and Tara Buentello -- The "Nuevo South" : Latino place making and community building in the middle-ring suburbs of Charlotte / Heather A. Smith and Owen J. Furuseth -- Afterword : coming to terms with federal and local immigration reform / Audrey Singer, Susan W. Hardwick, and Caroline B. Brettell.
Includes bibliographical references and index.
Keywords: Immigrants -- United States; Social integration -- United States; Suburbs -- United States; Metropolitan areas -- United States; United States -- Emigration and immigration -- Social aspects